2019
DOI: 10.14507/epaa.27.4597
|View full text |Cite
|
Sign up to set email alerts
|

Logics of accountability: Cross-national patterns in school-level controls

Abstract: This paper explores multiple logics of accountability by examining patterns of control of various school functions under different accountability systems. Research has shown that accountability is a global phenomenon, but how accountability is understood and enacted is locally contextualized, which implies the existence of multiple logics of accountability in practice. By linking theoretical arguments rooted in literature to empirical evidence observed in TALIS 2013, we aim to theorize logics of accountability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…On one hand, research on school reform and improvement has examined decentralized governance regarding decision-making at the school level. School autonomy and its role as a driver of desired school outcomes and improvements (Kim & Yun, 2019;Hanushek et al, 2013;Malen et al, 1990;Mwinjuma et al, 2015). The rationale of such efforts being that people who closely interact with students and school communities can better identify local needs and resources (Malen et al, 1990;Wohlstetter et al, 2013;Wohlstetter & Odden, 1992).…”
Section: School and Principal Autonomymentioning
confidence: 99%
See 2 more Smart Citations
“…On one hand, research on school reform and improvement has examined decentralized governance regarding decision-making at the school level. School autonomy and its role as a driver of desired school outcomes and improvements (Kim & Yun, 2019;Hanushek et al, 2013;Malen et al, 1990;Mwinjuma et al, 2015). The rationale of such efforts being that people who closely interact with students and school communities can better identify local needs and resources (Malen et al, 1990;Wohlstetter et al, 2013;Wohlstetter & Odden, 1992).…”
Section: School and Principal Autonomymentioning
confidence: 99%
“…As accountability has become a global norm in education policy over the past three decades (Kim & Yun, 2019;Grinshtain & Gibton, 2018;Gobby, 2013;Keddie, 2016), research has reported high pressures and tensions on principals' use of autonomy in schools combined with complex metrices of accountability. Such tensions are particularly salient in the US, as federal, state, and local controls are continually added to school-based accountability measures throughout policy trajectories (e.g., NCLB and ESSA).…”
Section: School and Principal Autonomymentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 50 countries, high achieving students in countries with test-based accountability policies were less likely to expect to work as teachers, suggestive of the greater hurdle to attract top talent to the teaching profession (Han 2018). Third is a transformed discourse on the amount of state control over local institutions and professions, like schools and teachers (Ingersoll and Collins 2017;Kim and Yun 2019), highlighting the increased incursion of state oversight and the naturalization of this practice. A fourth discourse can revolve around placing the blame of inequality on schools rather than larger structural forces (Diamond and Spillane 2004).…”
Section: Accountability Beyond the Schoolmentioning
confidence: 99%
“…Some countries such as the United Kingdom and Chile have similar performance‐based accountability systems with material consequences (Munoz‐Chereau, González, and Meyers 2020), while other countries such as Colombia, Norway, and Denmark have soft accountability regimes that publicly post school results but do not tie direct incentives or sanctions (Diaz Rios 2020; Verger, Fontdevila, and Parcerisa 2019). While the practice of school accountability has been scaled up and down across the years and has taken different forms across contexts, these only emphasize its being a persistent, consequential, and dynamic transnational agenda (Holloway, Sørensen, and Verger 2017; Kim and Yun 2019). In this essay, “school accountability” is focused on both school and teacher accountability systems in basic education (i.e., kindergarten to 12 th grade).…”
mentioning
confidence: 99%